Ammonia decomposition over Ru catalysts supported on alumina with different crystalline phases - Kim, Han Bom; Park, Eun Duck (Catalysis Today, 2023)
The effect of the crystalline phase of alumina on ammonia decomposition over alumina-supported ruthenium (Ru) catalysts was examined. Various Ru catalysts supported on different alumina (α-Al2O3, κ-Al2O3, θ-Al2O3, δ-Al2O3, η-Al2O3, and γ-Al2O3) were prepared using a wet impregnation method. The prepared catalysts were characterized using inductively coupled plasma-optical emission spectroscopy, N2 physisorption, X-ray diffraction, transmission electron microscopy, and CO chemisorption. The Ru dispersion for Ru/Al2O3 was reduced without a calcination step in the following order: Ru/α-Al2O3 < Ru/κ-Al2O3 < Ru/θ-Al2O3 < Ru/δ-Al2O3 < Ru/η-Al2O3 < Ru/γ-Al2O3. Among them, Ru/α-Al2O3 showed the highest catalytic activity for ammonia decomposition. Moreover, the effect of calcination temperature before the reduction step was investigated. Ru particle size and morphology were confirmed to change through the calcination process. Ru/κ-Al2O3 with Ru particle sizes ranging between 7 and 8 nm exhibited the highest ammonia decomposition rate among Ru/Al2O3 catalysts calcined at different temperatures and reduced at 573 K. Therefore, Ru dispersion and its morphology, which can be controlled by the support and calcination temperature, are critical factors for hydrogen production through ammonia decomposition over Ru/Al2O3 catalysts.
Keywords: Alumina phase; Alumina-supported; Ammonia decomposition; Calcination temperature; Crystalline phasis; Ruthenium catalysts; Ruthenium size; Ruthenium/al2O3; Wet impregnation method; Alumina phase; Ammonia decomposition; Hydrogen production; Ru size; Ru/Al2O3